Hypoglycaemic Activity of Flavonoid Isolate from Cereus Pterogonus Lemaire - Ragunathan, V.; Mohan Kumar, K.; Sankar, A. (Asian Journal of Chemistry, 2011)
The flavonoid glycoside isolated from cereus pterogonus Lemaire possesses hypoglycaemic activity. The aglycone is myricetin-5'-O-methyl ether and the sugars are glucose and rhamnose. All these were characterized by UV, 1H NMR, 13C NMR and MS studies.